MIGRASI TENAGA KERJA DARI SEKTOR PERTANIAN KE NON PERTANIAN DI DESA TATELU KECAMATAN DIMEMBE - Nita Novita Tulangow; Nordy F. L. Waney; Jean F. J. Timban (AGRI-SOSIOEKONOMI, 2017)
This study aims to (1) find out the factors that affect the occurrence of labor migration in the villageTatelu, Dimembe Sub-district, North Minahasa Regency, (2) to know the socio-economic background of labormigration from agriculture to non agricultural. (3) to know whether after changing the expectation of labor isrealized. This study was conducted from February to April 2016 in Tatelu Village, Dimembe District, NorthMinahasa Regency. Data collections have used survey method. Techniques of collecting data throughinterviews used a questionnaire. Sources of data in this study were labor migrants who moved fromagriculture to non-agricultural sectors. Secondary data is obtained from Tatelu Village office government. Thesampling technique uses purposive sampling. The variables measured in this study were (1) Revenue, (2)Education level, (3) Area of agricultural land, (4) Occupational conditions in non-agricultural, (5) Reasonsfor labor migration, (7) Number of dependents, (8) Social activities that are usually followed by labor in thevillage. Data Analysis Method used Primary data obtained is processed descriptively. The results showed (1)the factors that encourage the migration of labor from agriculture to non-agriculture namely; reducedagricultural land, low wages in agriculture, age, and non-farm employment are more promising, (2) Most ofthe respondents who follow social activities in the village of Tatelu such as harmonious because in addition tobeneficial for the respondent can also strengthen the rope fraternity among members of the rukun. Byparticipating in the rukun in the village, the respondent must have more income because they have to spendmoney in every meeting that is always held. (3) After migrating from agriculture to non-agricultural sector, allexpectation of interviewed respondents is realized because besides earning big enough they also feelcomfortable working in non-agricultural sector.